Vertically stacked monolithic perovskite colour photodetectors - Sergey Tsarev; Daria Proniakova; Xuqi Liu; Erfu Wu; Gebhard J. Matt; Kostiantyn Sakhatskyi; Lorenzo L. A. Ferraresi; Radha Kothandaraman; Fan Fu; Ivan Shorubalko; Sergii Yakunin; Maksym V. Kovalenko (Nature, 2025)
Abstract Modern colour image sensors face challenges in further improving sensitivity and image quality because of inherent limitations in light utilization efficiency 1 . A major factor contributing to these limitations is the use of passive optical filters, which absorb and dissipate a substantial amount of light, thereby reducing the efficiency of light capture 2 . On the contrary, active optical filtering in Foveon-type vertically stacked architectures still struggles to deliver optimal performance owing to their lack of colour selectivity, making them inefficient for precise colour imaging 3 . Here we introduce an innovative architecture for colour sensor arrays that uses multilayer monolithically stacked lead halide perovskite thin-film photodetectors. Perovskite bandgap tunability 4 is utilized to selectively absorb the visible light spectrum’s red, green and blue regions, eliminating the need for colour filters. External quantum efficiencies of 50%, 47% and 53% are demonstrated for the red, green and blue channels, respectively, as well as a colour accuracy of 3.8% in Δ E Lab outperforming the state-of-the-art colour-filter array and Foveon-type photosensors. The image sensor design improves light utilization in colour sensors and paves the way for the next generation of highly sensitive, artefact-free images with enhanced colour fidelity.